Epidemiology of urticaria in Poland – nationally representative survey results - Raciborski, Filip; Kłak, Anna; Czarnecka-Operacz, Magdalena; Jenerowicz, Dorota; Sybilski, Adam; Kuna, Piotr; Samoliński, Bolesław (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2018)
Introduction : The prevalence of urticaria is 15–20%. Women are twice as likely to be affected. Aim : To present the epidemiology of urticaria and angioedema in Poland. Material and methods : A questionnaire-based survey was conducted on a representative group of 4,897 individuals, aged 15–74 years. Results : A total of 11.2% of respondents reported at least one episode of urticaria symptoms in their life, and the frequency was higher in females (OR = 1.46; p < 0.001). Single episodes accounted for 34.8%, while repeated episodes accounted for 65.2%. Acute urticaria was observed in 10.6% (more frequent in females; OR = 1.41; p < 0.001), chronic in 0.6%. Median age of the first episode was 15 years. Angioedema was observed in 3.2%. The last episode of urticaria symptoms and/or angioedema occurred within the previous week in 0.7% of subjects, the last month in 1%, and the last year in 2.2%. 8.8% had experienced urticaria symptoms or angioedema over 1 year prior to the survey. The impact of urticaria symptoms on patients’ daily activities was rated with 3.8 points on a scale of 0–10. In addition, chronic urticaria was rated 6.5, and acute urticaria 3.6. Angioedema and urticaria had a negative impact of 5.7 points. Conclusions : Urticaria and angioedema are serious health problems in Poland, although their prevalence is below the mean rate for the global population. Females are more likely to suffer from these diseases. People affected by urticaria most frequently report contact with plants and substances, insect bites/stings, and food as the provoking factors.